Percutaneous coronary intervention versus coronary bypass surgery for unprotected left main disease: a meta-analysis of randomized controlled trials - Rahouma, Mohamed; Abouarab, Ahmed; Franco, Antonino Di; Leonard, Jeremy R.; Lau, Christopher; Kamel, Mohamed; Ohmes, Lucas B.; Girardi, Leonard N.; Gaudino, Mario (Annals of Cardiothoracic Surgery; Vol 7, No 4 (July 31, 2018): Coronary Revascularisation—Cardiology for the Surgeon, 2018)
Background: This meta-analysis of randomized controlled trials (RCTs) was aimed at comparing coronary artery bypass grafting (CABG) with percutaneous coronary intervention (PCI) for the treatment of unprotected left main coronary disease. Methods: All RCTs randomizing patients to any type of PCI with stents vs. CABG for left main disease (LMD) were included. Primary outcome was a composite of follow-up death/myocardial infarction/stroke/repeat revascularization. Secondary outcomes were peri-procedural mortality and the individual components of the primary outcome. Incidence rate ratio (IRR) or odds ratio (OR) and 95% confidence intervals (CIs) were pooled using a generic inverse variance method with random effects model. Subgroup analyses were done based on: (I) type of PCI [bare metal stents (BMS) vs. drug-eluting stents (DES)] and; (II) mean SYNTAX score tertiles. Leave one-out analysis and meta-regression were performed.< Results: Six trials were included (4,700 patients; 2,349 PCI and 2,351 CABG). Follow-up ranged from 2.33 to 5 years. PCI was associated with higher risk of follow-up death/myocardial infarction/stroke/repeat revascularization (IRR =1.328, 95% CI, 1.114–1.582, P=0.002) and of repeated revascularization (IRR =1.754, 95% CI, 1.470–2.093, P